Case Report: Drug-Induced (Neuro) Sarcoidosis-Like Lesion Under IL4 Receptor Blockade With Dupilumab - Tsitos, Stergios; Niederauer, Lisa Catherina; Albert i Gracenea, Paula; Mueller, Johanna; Straube, Andreas; Von Baumgarten, Louisa (Frontiers in Neurology, 2022)
Dupilumab is a new monoclonal antibody inhibiting IL-4 and IL-13 signaling transduction through the blockage of the α-subunit of the IL-4 receptor. It is used to treat type 2 inflammatory disorders including atopic dermatitis, asthma and chronic rhinosinusitis. Here we describe the case of a 79-year-old male presenting with visual hallucinations, disorientation, cognitive decline and behavioral changes, evolving over 3 weeks. He had been under treatment with dupilumab for atopic dermatitis for the previous 4 months. Radiology and CSF analysis showed a granulomatous meningoencephalitis suspicious for sarcoidosis. Underlying infectious and antibody-mediated causes for meningoencephalitis were ruled out. Pausing of Dupilumab and steroids (i.v. and oral) led to rapid clinical improvement. Inhibition of IL-4 and IL-13, key players in the differentiation and activation of Th2 cells, may shift the Th1/Th2- ratio towards an excessive Th1-mediated response, granuloma formation and drug-induced (neuro)sarcoidosis reaction. Attention should be raised to this side effect.